(3cja JhGLg Gdbdb ? Ybdj dG jgOCs - (3YHOGdeMSf, QjgGes; (3UdGM, eQhIs; (3YHOGdeYR, SGdes; (3OGQ MhGOjJ ddfTQ hGdJhRjYs ((3GdefhajI, eUQs (3MhGOjJ ddfTQ hGdJhRjYs, 2021)
(3Gdbdb hGdJhJQ ef GdeTGYQ GdEfSGfjI GdWHjYjI, hdcfgG bO Jchf SHH ai YOe GdbOQI Ydi GdbjGe HGdCYeGd GdWHjYjI, MjK CQSd bGQF jbhd CYGfi CMjGfG ef Gdbdb hGdJhJQ hGdPi bO jSHH GVWQGH Gdfhe hPdc EPG cfJ efTZd GdHGd HGdbjGe HCOGA Yed ege Ch Cffi Ydi hTc GLJjGR GeJMGf Ch ebGHdI Yed ai GdUHGM eeG jDKQ HGdSdH Ydi MUhdi Ydi GdJQcjR GdcGai CQLh JhVjM NWhGJ aYGdI ddJZdH Ydi gPg GdeTcdIs
Keywords: (3GdEQTGO GdfaSjs; (3GdEVWQGHGJ GdfaSjIs; (3GdUMI GdfaSjIs; (3Gdbdbs